Monitoring and modifying recruitment and retention strategies for an ongoing randomised clinical trial with venous leg ulcer patients: Overcoming barriers to participation - McDaniel, Jodi Christine; Rausch, Jamie Ann; McGowan, Dina Rose (International wound journal, 2023)
Venous leg ulcers (VLUs) are open skin lesions of the lower legs arising in areas affected by venous hypertension that are associated with substantial morbidity. Clinical trials testing innovative approaches to improve healing outcomes are critically needed because standard therapies are often ineffective. However, patients with VLUs frequently have multiple physical, emotional and socioeconomic challenges that can negatively impact their decision to enrol in a clinical trial. To benefit clinical researchers and ultimately the community of patients with chronic wounds, this paper describes the monitoring and modification of recruitment strategies in an ongoing clinical trial testing effects of omega‐3 fatty acid oral supplementation on VLU healing in ageing adults (n = 208). Multiple modifications over time in this study have targeted participation barriers identified through data monitoring and include expanding inclusion criteria, adding recruitment sites, enhancing communication methods, and meeting patients' transportation needs. Recruitment activities from January 2019 to June 2022 have resulted in 57 participants (mean age: 63.7 years). Overall, the recruitment rate is 42.5% of patients contacted during face‐to‐face visits. Overcoming barriers to participation is key to helping patients with VLUs interested in research enrol in clinical trials aiming to improve healing outcomes in this vulnerable population.